Broad-scale spatial distribution, microhabitat association and habitat partitioning of damselfishes (family Pomacentridae) on an Okinawan coral reef - Nanami,Atsushi (PeerJ, 2025)
Spatial distribution of coral reef fishes is related to diverse environmental variables. This study aimed to elucidate the (1) broad-scale spatial distribution, (2) microhabitat-scale substrate association, (3) degree of dependence on live corals and (4) habitat partitioning of 26 damselfish species on an Okinawan coral reef. Broad-scale analysis revealed that fish assemblages could be divided into three groups in relation to the degree of wave exposure, and the coverage of live corals as well as non-coralline substrates: (1) 11 species that were found in exposed reefs with greater coverage of rock; (2) nine species that that were found in inner reefs with greater coverage of live corals, dead corals and macroalgae; and (3) six species that were found in inner reefs with a greater coverage of sand. Microhabitat-scale analysis revealed that fish assemblages could be divided into six groups in relation to diverse microhabitat availability: (1) 12 species showed significant positive associations with rock; (2) two species showed significant positive associations with coral rubble; (3) two species showed significant positive associations with corymbose Acropora, Pocillopora and branching corals; (4) three species showed significant positive associations with branching Acropora; (5) three species showed significant positive associations with branching Acropora, branching Isopora and branching Porites; and (6) two species showed significant positive associations with staghorn Acropora and branching Millepora. The microhabitat-scale analysis also revealed that Pomacentrus amboinensis showed a significant positive association with branching Millepora, whereas Neopomacentrus anabatoides showed significant positive associations with branching Porites, foliose coral and dead branching Porites. Among the 26 species, nine species were categorized as obligate coral dwellers (>80% of the individuals were associated with live corals), and three species showed a greater degree of dependence on acroporid corals (>60% individuals were associated with acroporid coral). Niche overlap analysis revealed that 14 species showed relatively greater habitat partitioning with other species, whereas the remaining 12 species showed greater habitat overlaps among some species. These results suggest that broad-scale and microhabitat-scale habitat partitioning is one of the factors supporting coexistence in at least 14 species among the 26 species, and the effects of habitat diversity on the species coexistence of damselfishes should be incorporated to establish effective marine protected areas to preserve damselfish species diversity.
Keywords: Broad-scale spatial distribution; Microhabitat association; Habitat partitioning; Damselfish; Substrate characteristics; Coral reef